Arah Kebijakan Hukum Politik Ekonomi - Mardalena Hanifah (Fakultas Hukum Universitas Riau, 2012)
Law and economics are the pillars of development so that both must be matched and aligned with the interests of the people. Thus the legal policy direction of economic policy should be something that has value in order for legal purposes can be achieved.